Combined use of electron microscopy and intravital imaging captures morphological and functional features of podocyte detachment - Burford, James L.; Kriz, Wilhelm (Pflügers Archiv, 2017)
The development of podocyte injury and albuminuria in various glomerular pathologies is still incompletely understood due to technical limitations in studying the glomerular filtration barrier (GFB) in real-time. We aimed to directly visualize the early morphological and functional changes of the GFB during the development of focal segmental glomerulosclerosis (FSGS) using a combination of transmission electron microscopy (TEM) and in vivo multiphoton microscopy (MPM) in the rat puromycin aminonucleoside (PAN) model. We hypothesized that this combined TEM + MPM experimental approach would provide a major technical improvement that would benefit our mechanistic understanding of podocyte detachment. Male Sprague-Dawley (for TEM) or Munich-Wistar-Frömter (for MPM) rats were given a single dose of 100-150 mg/kg body weight PAN i.p. and were either sacrificed and the kidneys processed for TEM or surgically instrumented for in vivo MPM imaging at various times 2-14 days after PAN administration. Both techniques demonstrated hypertrophy and cystic dilatations of the subpodocyte space that developed as early as 2-3 days after PAN. Adhesions of the visceral epithelium to the parietal Bowman’s capsule (synechiae) appeared at days 8-10. TEM provided unmatched resolution of podocyte foot process remodeling, while MPM revealed the rapid dynamics of pseudocyst filling, emptying, and rupture, as well as endothelial and podocyte injury, misdirected filtration, and podocyte shedding. Due to the complementary advantages of TEM and MPM, this combined approach can provide an unusally comprehensive and dynamic portrayal of the alterations in podocyte morphology and function during FSGS development. The results advance our understanding of the role and importance of the various cell types, hemodynamics, and mechanical forces in the development of glomerular pathology.